Flamboyant in Bloom - Royal Botanic Gardens, Port of Spain, Trinidad, B.W.I. - Dalla Costa, H. (Y. De Lima and Co. Ltd., Trinidad, 2009)
A picture of a woman standing next to a car parked on the road outside the Botanical Gardens looking at a Flamboyant Tree in bloom. Postcard number K 5142.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Trees--Trinidad and Tobago; Botanical gardens--Trinidad and Tobago; Royal poinciana--Trinidad and Tobago; Automobiles--Trinidad and Tobago; Women--Trinidad and Tobago